2019
DOI: 10.1177/0020852319861895
|View full text |Cite
|
Sign up to set email alerts
|

A review of the generic end-user adoption of e-government services

Abstract: E-government projects provide many advantages and offer benefits to governments and their citizens. Hence, the big issue and challenge for governments are how they can increase citizen adoption. This has resulted in the development of many e-government initiatives that aim to enhance the provision of public services to citizens and improve associations with industry and world business. It is shown that there are critical success factors and barriers in e-government adoption, and technology adoption more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Moreover, trust [154], especially in the government and in the nature of the perceived quality of the service, are key tools as well [155,159]. The current reality puts us in an unresolved problem of e-government adoption, as the web pages still do not meet the citizens' expectations [150], being the rural inhabitants the least prone to use them [160]. As a result, we believe that the elaboration of studies focused on rural areas has an exponential value and relevance nowadays, since it is essential to take into account the importance of the rural world, more concretely of dairy farms, in the production and supply of the worldwide population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, trust [154], especially in the government and in the nature of the perceived quality of the service, are key tools as well [155,159]. The current reality puts us in an unresolved problem of e-government adoption, as the web pages still do not meet the citizens' expectations [150], being the rural inhabitants the least prone to use them [160]. As a result, we believe that the elaboration of studies focused on rural areas has an exponential value and relevance nowadays, since it is essential to take into account the importance of the rural world, more concretely of dairy farms, in the production and supply of the worldwide population.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of that, there still exist critical factors of success, barriers to the adoption of the electronic government and of technology in general, which make clear the fact that the current models do not fulfill the citizen's needs and expectations [149,150]. Related to this situation, we find the scarce involvement of the possible users in the designing process [151].…”
Section: Administration (36 Documents)mentioning
confidence: 97%
“…These results are closely related to those obtained by [50] based on UTAUT and UMEGA, where it is observed that the nature of the perceived quality of the service and, in addition, the trust in the government are fundamental to determine the intention of use. This situation demonstrates that there are still critical success factors and that the current models do not meet the citizens' needs and expectations [84]. We also have to take into account the poor connection conditions, which hamper the inclusion of the new technologies in their activity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if there are patients who are positive for Covid-19, special isolation is needed to reduce the possibility of transmission (Niud & Fu, 2020;Hellewell et al, 2020) In recording positive data on the Covid-19 case, the government certainly needs technology to store this data to be used as information. Therefore, the role of information systems is needed in this case (Berlilana et al, 2018;Jacob et al, 2019). To assist the role of the government in determining optimal policies and information systems, various media is needed that make the Covid-19 information center accessible to the wider community (Shiferaw et al, 2017).…”
Section: Introductionmentioning
confidence: 99%